Analisis Sentimen Pemilihan Presiden 2019 pada Twitter menggunakan Metode Maximum Entropy - Alvandi Fadhil Sabily; Putra Pandu Adikara; Mochammad Ali Fauzi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In this modern era, communication can be done through various media, one of which is through online media, namely Twitter. Twitter is one of the social media that functions to exchange information and also express an opinion on something. Twitter posts that discuss presidential elections are the objects used in this study. To find out whether a sentiment has a positive or negative value, a sentiment analysis is needed as in this study. To analyze a sentiment, a method that can classify sentiments is needed, Maximum Entropy is the method used in this study with the evaluation method used is Confusion Matrix which will then calculate the value of Macro and Micro averaging from the evaluation value produced. The evaluation results carried out in this study resulted in quite high Macro accuracy values ​​of 89.16% with precision and recall values ​​of 100% and 89.16% and also F-measure values ​​of 94.27%. Testing is done by testing 120 tweets and training data used as many as 300 tweets.